Urartian Wall Painting Fragment with Three Warriors from Erebuni: Archaeological Context, Attribution, and Iconography - Vergazov, Ramil R. (Actual Problems of Theory and History of Art, 2023)
A mural fragment depicting three warriors has been found during the excavations of the Urartian fortress of Erebuni by a joint archaeological expedition of the Academy of Sciences of the Armenian SSR, the Pushkin State Museum of Fine Arts, and the Department for the Protection of the Gosstroy of the Armenian SSR in 1965. The fragment was discovered in the large hall of the palace of Argishti I (the so-called “room No. 15”), the excavations of which were carried out by a detachment of the Pushkin State Museum of Fine Arts. The group of wall paintings from “room No. 15” has its special character. In addition to the classic Urartian multi-tiered compositions of the 8th century B. C., there are unique scenes, so-called ‘secular paintings’, which have otherwise never been found in the monumental art of Urartu. The mural fragment with three warriors belongs to this group.Despite repeated publications on the monument, the archaeological context of this fragment has never been elucidated, which is why different opinions arose in the literature about its attribution. During the study of the archaeological archive of the Pushkin State Museum of Fine Arts detachment, the author has managed to find information about the archaeological context of this mural fragment and to establish the cultural layer within which it was discovered. The obtained archival data, the results of the new excavations at Arin-berd, together with the analysis of iconography, allowed us to offer our reasoned attribution of the fragment of the painting with three warriors, which, in our opinion, belongs to the late Urartian ‘secular’ wall painting style of the middle – last third of the 7th century B. C.
Keywords: wall paintings; mural with three warriors; Urartu; Erebuni; excavations of Arin-berd; detachment of the Pushkin State Museum of Fine Arts; iconography; attribution; archival materials